Patients with rheumatoid arthritis have impaired long-term outcomes after myocardial infarction: a nationwide case-control registry study - Palomäki Antti; Kerola Anne M; Malmberg Markus; Rautava Päivi; Kytö Ville (United Kingdom, 2022)
Objective: To investigate the long-term outcomes of patients with RA after myocardial infarction (MI).
Methods: All-comer, real-life MI patients with RA (n = 1614, mean age 74 years) were retrospectively compared with propensity score (1:5) matched MI patients without RA (n = 8070) in a multicentre, nationwide, cohort register study in Finland. The impact of RA duration and the usage of corticosteroids and antirheumatic drugs on RA patients' outcomes were also studied. The median follow-up was 7.3 years.
Results: RA was associated with an increased 14-year mortality risk after MI compared with patients without RA [80.4% vs 72.3%; hazard ratio (HR) 1.25; CI: 1.16, 1.35; P <0.0001]. Patients with RA were at higher risk of new MI (HR 1.22; CI: 1.09, 1.36; P =0.0001) and revascularization (HR 1.28; CI: 1.10, 1.49; P =0.002) after discharge from index MI. Cumulative stroke rate after MI did not differ between RA and non-RA patients (P =0.322). RA duration and corticosteroid usage before MI, but not use of methotrexate or biologic antirheumatic drugs, were independently associated with higher mortality (P <0.001) and new MI (P =0.009). A higher dosage of corticosteroids prior to MI was independently associated with higher long-term mortality (P =0.002) and methotrexate usage with lower stroke rate (P =0.034). Serological status of RA was not associated with outcomes.
Conclusion: RA is independently associated with poorer prognosis after MI. RA duration and corticosteroid usage and dosage were independent predictors of mortality after MI in RA. Special attention is needed for improvement of outcomes after MI in this vulnerable population.